Clinical phenotypes of adult atopic dermatitis and related therapies. Issue 4 (28th August 2022) - Patruno, Cataldo; Potestio, Luca; Napolitano, Maddalena
Abstract : Purpose of review: To report current knowledge on the different clinical phenotypes of adult atopic dermatitis. Possible therapeutic intervention in relation to phenotype is also evaluated. Recent findings: Atopic dermatitis is a chronic inflammatory disease affecting up to 10% of adults. It can manifest with different clinical phenotypes, causing diagnostic difficulties. Long-term is often required and systemic drugs are needed for moderate-to-severe forms. However, few drugs are registered for atopic dermatitis in many countries. Furthermore, limited data exist regarding the treatment in relation to individual clinical phenotypes. Summary: Currently, the most relevant data are those for cyclosporine, alitretinoin, and dupilumab. Cyclosporine and dupilumab showed to be effective in the treatment of atopic dermatitis, although in trials and real-life experiences the different phenotypes treated are usually not reported. However, cyclosporine appears to be effective in prurigo nodularis. Alitretinoin is reported to be particularly efficacious for atopic dermatitis of the hands, while it is ineffective for other locations of the disease. Dupilumab demonstrated its efficacy in prurigo nodularis and nummular eczema phenotypes of atopic dermatitis; moreover, especially in elderly patients, its effectiveness seems to be faster if the folds of the limbs are involved.